KEKERASAN TERHADAP PEREMPUAN - Abidin, Kurniati (PSW, 2012)
This paper examines the causes of violence against woman. The reason the author of this paper raised since woman tend to be the object of violence in their lives that resulted in physical and non-physical effects for victims. There are three factors contributing to violence against woman, the biological factors, frustration-aggression, and learning factors. Comprehensive solutions to prevent violence focuses on the perpetrators and victims of violence.